An Open-label Randomized Comparative Clinical Trial of Indravati and Vangeshwara Rasa in the Patients Suffering from Madhumeha (Type 2 Diabetes) - Kanchan Swami; Karunanidhi Sharma; Sanjay Kumar (Journal of Ayurveda)
Introduction:Diabetes, is a metabolic disorder and a leading health problem in the world, manifested by increased blood glucose levels and symptoms such as polyphagia, polydipsia, and polyuria. Madhumeha (a type of Prameha) is a disease condition, described in Ayurveda that can be correlated with Diabetes type 2, has similar features and prognosis. For Madhumeha number of herbal and herbomineral formulations are reported in the Ayurvedic text, Indra Vati (IV) and Vangeshwara Rasa (VR) are two of them. IV contains Rasasindoora, Vanga Bhasma, Terminalia arjuna, and Salmalia malabarica whereas VR has Rasasindoora and Vanga Bhasma. The present study was planned to compare the efficacy of both formulations in the clinically diagnosed subjects of Madhumeha when given on classically mentioned doses. Methods:Forty clinically diagnosed patients of Madhumeha were randomly divided into two Groups. Group A was treated with IV in the dose of 62.5 mg, whereas Group B was with VR in dose of 125 mg. In both groups, drugs were given before meal twice a day with lukewarm water for 2 months (60 days). Effect of both the drugs was evaluated and compared on subjective and objective parameters. Result:Both the drugs showed promising results on most of the parameters, but when compared VR showed better efficacy than IV in the overall effect of therapies. This may be because of the better effectivity of Rasasindoora and Vanga Bhasma present in higher quantities in VR than in IV. Conclusion:VR has better efficacy on Madhumheha (Diabetes type 2) than IV on the classically mentioned dose.